Algebraic Approach to Geometric Quantum Speed Limits in Triatomic Molecules (Journal of Atomic and Molecular Sciences, 2016)
The appropriate metric of quantum speed limit for the triatomic moleculesis discussed using a generalized geometric approach. The researches show the quantumFisher information metric is tighter than the Wigner-Yanase information metric inrealistic molecular dynamical evolution. The quantum speed limit metric is related tothe initial evolution state of molecules.